Ankle brachial index and foot ulcer risk stratification among outpatients with type 2 diabetes mellitus at a public referral hospital in South India: a preventive perspective - Mathew, Sheeba; Elavally, Sujitha; Madhavan, Indira; Prabhakaran, Geethakumary V.; Mathew, Sheeja (International Surgery Journal, 2025)
Background: Peripheral artery disease is perceived to reduce blood flow to the lower extremities of patients with diabetes and lead to foot ulcers. This research investigated the possible association of ankle brachial index (ABI) with foot ulcer risk (FUR), as well as the associations of both with socio-clinical variables among a group of patients with type 2 diabetes mellitus (T2DM). Methods: 236 patients who regularly visited the outpatient department of a public tertiary care centre in South India were enrolled. ABI was studied using a hand-held Doppler-HI. dop 2.4.5.8 MHz. Foot ulcer risk was measured using INLOW’S 60-second diabetic foot screen. Other related socio-clinical variables were also collected. Results: The mean age of the patients was 56.06±8.09 years. The mean ABI was 1.01 (±0.15). 3.38% presented with critical limb ischemia. One fourth of the patients belonged to the high to urgent FUR category. ABI was associated with gender and alcohol consumption. FUR was associated with religion, education, history of foot ulcer or amputation, presence of foot ulcer, diabetic retinopathy, regular foot care and follow-up habits, HbA1C, serum urea, and creatinine. Median ABI scores differed significantly across FUR categories (Kruskal–Wallis H 13.09, p value 0.011). Conclusions: ABI among patients with T2DM was related to FUR, and both these variables demonstrated different association patterns with socio-clinical variables, with no shared significant associations. Outpatient-based Doppler study is feasible and may be a useful initiative to identify the foot ulcer risk in advance.